PENGGUNAAN BAHASA INDONESIA DALAM UNDANG-UNDANG ORGANISASI KEMASYARAKATAN DI INDONESIA - Siti Nailus Masrihah; Syamsul Ghufron (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2020)
This research was carried out with the aim of describing diction, sentence structure and meaning in the Ormas law. This research data is derived from the Republic of Indonesia Law Number 16 of 2017 concerning the stipulation of PERPPU Number 2 of 2017. Data was collected with documentation techniques, see, and record. Research findings show that (1) the use of diction is found in the types of generalizations, specifications, synonyms, connotations, and denotations, but there are no types of diction, popular, study, jargon, conversation, and slang. (2) sentence structure in the articles of the pros and cons there are basic sentences and transformational sentences. (3) the meaning of the articles of pro and contra is found in lexical, grammatical, conceptual, denotation, and connotation meanings.